THE INDIVIDUAL TAILORING OF IMMUNOSUPPRESSIVE THERAPY AFTER HEART TRANSPLANTATION - N. N. Koloskova; V. N. Poptsov; A. О. Shevchenko (Вестник трансплантологии и искусственных органов, 2018)
Heart transplantation is the «gold standard» of treatment severe heart failure. Immunosuppressive therapy aimed at the prevention of acute allograft rejection is the cornerstone of post-transplant management. In addition to its direct effects, immunosuppressive therapy is also involved in the generation of a number of post-transplant morbidities that limit the long-term outcome of heart transplant recipients. Given these data it appears that the individual tailoring of immunosuppressive therapy is of paramount importance in determining the outcome of heart transplantation. The goal of immunosuppressive therapy is to prevent rejection of the transplanted heart, while minimizing drug-related effects, such as infection, malignancy, diabetes, hypertension, and renal insuffi ciency. This review aimed is to analyze the protocols for the appointment of immunosuppressive therapy in various groups of recipients after heart transplantation.